2019
DOI: 10.1021/acs.chemmater.8b03977
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Valence State of Cu Dopant in α-Fe2O3 Anodes: Effects on Crystal Structure and the Conversion Reactions with Alkali Ions

Abstract: Doping is one of the most important ways to tailor the performance of energy materials. However, the crystal structure of doped materials is usually oversimplified as a simple substitution of dopants. Here, we characterized the doped α-Fe2O3 with different Cu cations using synchrotron X-ray diffraction, X-ray absorption, and X-ray photoelectron spectroscopy, and electrochemically evaluated it as an anode in lithium batteries. The results suggest that doping is not the simple replacement of Fe3+ sites by Cu2+ o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…The doping also induces the shift of O 1s signals toward lower binding energy from 529.9(1) to 529.6(1) eV (Figure 3f). Such shifts were not observed in Fe 2 O 3 with other divalent dopants, 12 and, thus, it is likely that the specific structure 34 The T M determined from the temperature-dependent magnetization under a field of 500 Oe is 249.5( 5) and 232.6(5) K under ZFC and FC, respectively (Figures 4a and S8). The antiferromagnetic coupling is significantly decreased by Mg doping, as characterized by the weak Morin transition and lower T M in Mg4 (Figure 4b,c), which is reduced to 197.6(5) and 142.7(5) K under ZFC and FC, respectively.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The doping also induces the shift of O 1s signals toward lower binding energy from 529.9(1) to 529.6(1) eV (Figure 3f). Such shifts were not observed in Fe 2 O 3 with other divalent dopants, 12 and, thus, it is likely that the specific structure 34 The T M determined from the temperature-dependent magnetization under a field of 500 Oe is 249.5( 5) and 232.6(5) K under ZFC and FC, respectively (Figures 4a and S8). The antiferromagnetic coupling is significantly decreased by Mg doping, as characterized by the weak Morin transition and lower T M in Mg4 (Figure 4b,c), which is reduced to 197.6(5) and 142.7(5) K under ZFC and FC, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…Despite the subtle structural change, the variation of the electronic configuration is suggested in some doped Fe 2 O 3 , generally resulting from the electron transfer or crystal-field splitting caused by dopants. According to density functional theory (DFT) calculations, the reduced Fe moments can be a result of Fe 3+ reduction to Fe 2+ by electron transfer from high-valent dopants (e.g., Ti 4+ and Sn 4+ ), though no Fe 2+ was observed experimentally in these doped materials . Furthermore, neutron diffraction experiments have shown that most of these doped Fe 2 O 3 still retain the antiferromagnetic ground state identical to that of Fe 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the peak at 950 eV and satellite peak at 956 eV corresponds to Cu 2p 1/2. In the end, XP spectra of Fe 2p was deconvoluted and found that it has two characteristic peaks at 712.3 eV and 724.4 eV for 2p 3/2 and 2p 1/2 with a peak separation of 12.1 eV which validate that catalyst contains iron as Fe 2+ [38,46] . More interestingly, the peak at 714.3 eV evidenced the presence of Fe 3+ as well (Figure 3f) which is in well agreement with the reported literature.…”
Section: Resultsmentioning
confidence: 95%
“…The strong peak at 0.63 V attributes to the formation of SEI layers which disappear in the next cycle and the peak at 0.75 V may be the attributed to the Li + insertion of MOx on the surface, whereas the broad peak is associated with the formation of a cubic Li–Fe–O phase because of Li insertion. [ 23 ] The CV curves of SSM‐MOx‐900 ( Figure a) change significantly: 1) The sharp reduction peak occurs between 0.01 and 0.3 V derived from the insertion of the formed hybrid MnO, SiO 2 , and Cr 2 O 3 ; 2) The reduction peaks of Fe 2 O 3 occur at 0.92 V; 3) The relative area of the CV curves of SSM‐MOx‐900 is much larger than that of SSM, indicating that the capacity density of SSM‐MOx‐900 is much larger than that of SSM. 4) The relative area of SSM‐MOx‐900 from the 1st cycle to the 2nd cycle is much smaller, reflecting the lower consumption of Li + during SEI formation.…”
Section: Resultsmentioning
confidence: 99%